(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article presents the thermal conductivity of various polymer materials. Thermoplastic polymers, especially high density polyethylene, polypropylene, and polymethyl methacrylate are described for their thermal conductivity under pressure. The change in thermal conductivity curves according to the type and amount of fillers added to thermoplastic polymers is explained by diagrams.